A Comparative Study on English Speaking Skill between Interpersonal and Intrapersonal Students in the Third Semester of English Teaching Learning Program of STAIN Pamekasan - Syafik, Moh; Raihany, Afifah (PANYONARA: Journal of English Education, 2020)
Students' different intelligence affect different academic achievement, speaking skill as one of the required skills that have to be mastered by students must also be influenced by students' intelligence. This study was mainly purposed to investigate whether there is a significant difference between interpersonal students and intrapersonal students on their English speaking skills. This study uses Ex-post facto or causal-comparative with a quantitative research approach. The population was 216 students of all third-semester students of English Teaching Learning Program of STAIN Pamekasan, the sample of 50 students (25 interpersonal students and 25 intrapersonal students) were taken away by using stratified random sampling. Two research instruments were utilized. The questionnaire was spread out to identify the students' intelligence, while documentation was used to know the result of the summative test of English speaking skills. The research result reveals there is a significant difference between interpersonal students and intrapersonal students in the third semester of the English Teaching Learning Program of STAIN Pamekasan on their English speaking skills. The t-value of 3.86 is significantly higher than the t-table (significant level 5%) that is only 2.01. (3.86 > 2.01; Level of significance 5%, df = 50). Interpersonal students are better on English speaking skills because they have special characteristics, such as love to interact, have good communication skills, strong empathy, and good sociability. They are usually outgoing and also easily adaptable make them quick to learn.